First observations of Weddell seals foraging in sponges in Erebus Bay, Antarctica - Rose T. N. Foster-Dyer; Kimberly T. Goetz; Matthew H. Pinkerton; Takashi Iwata; Rachel R. Holser; Sarah A. Michael; Craig Pritchard; Simon Childerhouse; Jay Rotella; Luisa Federwisch; Daniel P. Costa; Michelle A. LaRue (Polar Biology, 2023)
Attaching cameras to marine mammals allows for first-hand observation of underwater behaviours that may otherwise go unseen. While studying the foraging behaviour of 26 lactating Weddell seals ( Leptonychotes weddellii ) in Erebus Bay during the austral spring of 2018 and 2019, we witnessed three adults and one pup investigating the cavities of Rossellidae glass sponges, with one seal visibly chewing when she removed her head from the sponge. To our knowledge, this is the first report of such behaviour. While the prey item was not identifiable, some Trematomus fish (a known Weddell seal prey) use glass sponges for shelter and in which to lay their eggs. Three of the four sponge foraging observations occurred around 13:00 (NZDT). Two of the three sponge foraging adults had higher-than-average reproductive rates, and the greatest number of previous pups of any seal in our study population, each having ten pups in 12 years. This is far higher than the study population average of three previous pups (± 2.6 SD). This novel foraging strategy may have evolved in response to changes in prey availability, and could offer an evolutionary advantage to some individuals that exploit prey resources that others may not. Our observations offer new insight into the foraging behaviours of one of the world’s most studied marine mammals. Further research on the social aspects of Weddell seal behaviour may increase our understanding of the extent and mechanisms of behavioural transfer between conspecifics. Research into the specific foraging behaviour of especially successful or experienced breeders is also warranted.